Theo-anthroposentrism: An Answer to Criticm of the Theory of Anthroposentrism Environmental Ethics - Al Munir, M. Ied (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2023)
This study agrees that the theory of anthropocentrism environmental ethics has a weakness because it places human interests as a moral standard, but this research disagrees with the view that this weakness is influenced by religion. Conversely, religion is an important factor for the improvement of the theory of anthropocentrism environmental ethics. This study uses a qualitative method where data is obtained through tracking and reading various literature. The collected data were analyzed with hermeneutic and heuristic theories. This study found that the weakness of the theory of anthropocentrism environmental ethics lies in its scope which is only in the interests of humans. This weakness is seen as influenced by religious understanding that places humans as the center of the universe so that it gives rise to exploitative attitudes in humans. This view is wrong because in religion (Islam) humans are indeed given a high position, but with a great responsibility to protect nature. The reconstruction of this view leads to a new form of environmental ethics, namely theo-anthropocentrism in which it is hoped that humans can act wisely on the universe as God's representatives in the world.